(untitled) (Research, Society and Development, 2021)
The motivation of the construction of this narrative is to weave a reflection on the execution of the peripheral venous puncture procedure, taking as one of the foundations for this realization the adoption of mild, soft technologies as a device to minimize the fears and anxiety of patients before such a procedure. This study aimed to describe the experience of a nurse in the adoption of soft technologies in moments of pre and post-peripheral venous puncture, in an oncology outpatient clinic, incorporating the use of a strategy of light technologies like the use of practice associated with quality care. Relate of lived experience-reported in a more intense way during the pandemic period, in the oncology outpatient clinic of a public hospital in the southeastern region of Brazil. As a result, it was noticed the reduction of patient painful sensation after the venous puncture. We conclude that the adoption of soft technologies, also known as relational by the nursing team helps reducing fear of patients in the face of peripheral venous puncture, a fact that is consistent with the adoption of good practices and thus contributing to the promotion of these patients’ health.